Magnetization Transfer Imaging Is Unaffected by Decreases in Renal Perfusion in Swine. Issue 11 (November 2019) - Jiang, Kai; Ferguson, Christopher M.; Woollard, John R.; Landes, Vanessa L.; Krier, James D.; Zhu, Xiangyang; Nayak, Krishna S.; Lerman, Lilach O.
Abstract : Objectives: Multiparametric renal magnetic resonance imaging (MRI), including diffusion-weighted imaging, magnetic resonance elastography, and magnetization transfer imaging (MTI), is valuable in the noninvasive assessment of renal fibrosis. However, hemodynamic changes in diseased kidneys may impede their ability to measure renal fibrosis. Because MTI assesses directly tissue content of macromolecules, we test the hypothesis that MTI would be insensitive to renal hemodynamic changes in swine kidneys with acute graded ischemia. Materials and Methods: Seven domestic pigs underwent placement of an inflatable silicone cuff around the right renal artery to induce graded renal ischemia. Multiparametric MRI was performed at baseline, 50%, 75%, and 100% renal artery stenosis as well as reperfusion. Measurements included regional perfusion, R2 *, apparent diffusion coefficient (ADC), stiffness, and magnetization transfer ratio (MTR) using arterial spin-labeled MRI, blood oxygenation–dependent MRI, diffusion-weighted imaging, magnetic resonance elastography, and MTI, respectively. Histology was performed to rule out renal fibrosis. Results: During graded ischemia, decreases in renal perfusion were accompanied with elevated R2 *, decreased ADC, and stiffness, whereas no statistically significant changes were observed in the MTR. No fibrosis was detected by histology. After release of the obstruction, renal perfusion showed only partial recovery, associated with return of kidney R2 *, ADC, and stiffness to baseline levels, whereas cortical MTR decreased slightly. Conclusions: Renal MTI is insensitive to decreases in renal perfusion and may offer reliable assessment of renal structural changes.